(untitled) (African Journal of Biomedical Research, 2024)
This study compared mobile video instruction to face-to-face demonstrations in nursing practicum outcomes. Using quasi-experimental design, two nursing student groups were studied: UNTH-SON received mobile video instruction, while BS-SON had face-to-face demonstrations. Each group consisted of a randomly selected sample of 56 students (n=112). Prior to the intervention, a pre-test evaluated baseline skills, with the intervention group receiving a 30-minute video tutorial accessible on handheld electronic devices for three weeks, and the control group receiving twice-weekly 30-minute face-to-face sessions for the same duration. A post-test, conducted 21 days post-intervention, utilized a 39-item OSCE checklist with content validity of 0.902 and test-retest reliability of 0.817. Data were subjected to descriptive and inferential analysis (Student t-test and Fisher’s exact test) at a 5% significance level. Baseline skill assessment revealed the mobile video group’s mean score at 16.54 (5.46), with 82.1% performing poorly, compared to the face-to-face group’s mean score of 21.82 (6.72), with 64.3% performing poorly (p < 0.001). Post-intervention, the mobile video group scored 32.73 (5.49), with only 3.6% performing poorly, while the face-to-face group scored 33.23 (6.89), with 5.4% performing poorly (p = 0.627). Mobile video-based instruction exhibited a 42% higher effectiveness than face-to-face instruction, with a mean difference of 16.19 versus 11.41 (Effect Ratio 1.41). However, post-test scores showed no significant difference (p = 0.672). In conclusion, video-based teaching is effective for instructing basic nursing students in female urinary catheterization during educational practicum, especially when face-to-face demonstrations are impractical